The Glass Escalator and Gender Fatigue: Getting Gender back on the Agenda - Irene Kamberidou (Proceedings of the 5th International Conference on Interdisciplinarity in Education ICIE, 2010)
It seems we've come a long way since women‘s exclusion from the so-called male fields of the hard sciences. Women constitute over half the student population (52,9%) in the technological institutions in Greece and represent 58.7% of the total university student population. In the European Union (EU) 29.7 million women work in the science and technology (S&T) sectors, the highest percentage in Lithuania (72%) followed by Estonia (69.7%). On the other hand, the ―glass escalator (Hultin 2003, Williams 1992) is not yet gender inclusive since women today continue to be exceedingly under-represented in the workplace and especially in decision making positions: research, engineering, science and technology (S&T) and the academic hierarchies. An abundance of evidence indicates that men usually ride up the glass escalator as opposed to women who hit the glass ceiling and run into the ―sticky floor (Kimmel 2004). Gender diversity mainstreaming has given the impression that gender issues at work have been resolved, making subtle discrimination harder to spot. Current research indicates the need to focus on innovative approaches to getting gender back onto the agenda, namely to re-evaluate how we can move from ―gender fatigue (Kelan 2010, Merriman 2009) to gender energy. In examining international dialogue on the effects of the glass ceiling, the glass escalator and―gender fatigue, this paper discusses the 2009 ICT status report (European Commission 2010) which confirms that women’s interest in an academic career or in a career in the ICT sector is decreasing and presents an overview of the gender distribution in scientific research and in the academic hierarchies in Greece, where women still comprise a minority. Keywords: gender pay gap, glass escalator, glass ceiling, sticky floor, tokenism, gender fatigue.